Comparative Study on Consequences and Degree ofConviction of the Armenian Genocide in the Ottoman Empireand the Yezidi Genocide in Iraq - Marukyan, Armen (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Studying the consequences of various examples of genocide is important not only in terms of identifying the degree of their severity for the victim groups, but also in terms of clarifying the attitude of the international community towards these crimes at the time they were committed. It is important to understand what the position of the great powers was towards these crimes, whether it was expressed through simple condemnation, or certain measures were taken to stop the mass extermination of representatives of ethnic, racial, religious and national groups. From this point of view, in the context of comparing the consequences of the Armenian Genocide in the Ottoman Empire and the Yezidi Genocide in the region Sinjar of Iraq, the object of the given study is the reaction and degree of intervention of the international community, and influential actors in world politics, with the aim of stopping the further extermination of representatives of the victim groups of these crimes. To achieve the stated goals and objectives, the study combines historicalcomparative and analytical methods, uses a wide range of primary and secondary sources, as well as interdisciplinary research by specialists.
Keywords: History